La incorporación del aplicativo digital Flip para fortalecer la enseñanza y el aprendizaje en el curso de Introducción al Lenguaje Musical de la carrera de Música en una universidad de Lima - Lescano Contador, Juan Alfonso (2024)
The present proposal for educational innovation aims to address the difficulties faced by students in the Introduction to Musical Language (IML) course belonging to the music program of a university in Lima. Due to the lack of musical training with which they enter the program, many students encounter difficulties and challenges in IML, leading to high levels of stress, and either failing or dropping the subject. Therefore, this proposal aims to strengthen teaching and learning in IML through the incorporation of the Flip mobile application. Along the same lines, the specific objectives are to integrate playful and interactive activities requiring the use of Flip, update the teacher's knowledge about teaching through the application and its benefits, and encourage student self-learning through the use of smartphones. For this purpose, a pilot project was carried out in one of the course classrooms, with a sample group of 10 first-year students. The content was organized into files with activities and dictations to be carried out. The experience with the use of the application did not generate activity and participation. However, it managed to identify a series of relevant factors that will improve the educational and technological experience in IML. Among these are the development of student autonomy, a focus on the elaboration of musical dictations for ear training, and the incorporation of technological tools in course activities and assessments.